Direct sequencing of small genomes on the Pacific Biosciences RS without library preparation. (December 2012) - Coupland, Paul; Chandra, Tamir; Quail, Mike; Reik, Wolf; Swerdlow, Harold
We have developed a sequencing method on the Pacific Biosciences RS sequencer (the PacBio) for small DNA molecules that avoids the need for a standard library preparation. To date this approach has been applied toward sequencing single-stranded and double-stranded viral genomes, bacterial plasmids, plasmid vector models for DNA-modification analysis, and linear DNA fragments covering an entire bacterial genome. Using direct sequencing it is possible to generate sequence data from as little as 1 ng of DNA, offering a significant advantage over current protocols which typically require 400–500 ng of sheared DNA for the library preparation.